TEACHING READING COMPREHENSION THROUGH PEER TUTORING TECHNIQUE TO THE TENTH GRADE STUDENTS OF SMA SANTA MARIA KABANJAHE IN THE ACADEMIC YEAR OF 2020/2021 - Sembiring, Florentina; Lumban Raja, Viator; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2021)
The aims of this study are to prove whether Peer Tutoring Technique can improve studentsâ€™ reading comprehension and to know the studentsâ€™ responses after being taught by using Peer Tutoring technique. This research is Classroom Action Research (CAR) which was conducted by Teaching Reading Comprehension Through Peer Tutoring technique to the Tenth Grade Students of SMA Santa Maria Kabanjahe Class X IPA II in the Academic Year of 2020/2021. The quantitative data analysis showed that the studentsâ€™ mean score increased continuously from 46,42 in pre-test, 68,33 in formative test, and 80,38 in post-test. The percentage of the studentsâ€™ score increased from pre-test to post-test was 69,69%. The qualitative data analysis showed that the studentsâ€™ responses after being taught by using Peer Tutoring t echnique are very good. It can be seen from observation sheets and field notes; they felt more confident, enthusiastic and motivated to learn reading comprehension on narrative texts after Peer Tutoring technique was applied. The responses of students it can be seen from the total percentage of questionnaires strongly agree about 46,66% and followed by the highest percentage of agree about 46,06%. The Peer Tutoring technique wasÂ beneficial andÂ effectiveÂ forÂ teachingÂ readingÂ comprehension.Â ItÂ is suggestedÂ thatÂ EnglishÂ teachersÂ useÂ PeerÂ TutoringÂ techniqueÂ asÂ anÂ alternative techniqueÂ in teaching reading to the students in Senior High School in order to improve their studentsâ€™ reading comprehension.